Laparoscopic counterclockwise modular mesohepatectomy for hepatocellular carcinoma: a standardized anatomical approach (with video) - Chen, Xi; He, Wei; Wang, Jianjun; Kuang, Ming; Jiang, Ting; Luo, Hua; Hu, Zhaohui (Frontiers in Oncology, 2025)
BackgroundLaparoscopic liver resection (LLR) is increasingly utilized for hepatocellular carcinoma (HCC). However, laparoscopic anatomical resection of Couinaud segments 4, 5, and 8 remains technically demanding due to complex vascular anatomy and a broad transection plane.MethodsThis study retrospectively analyzed patients who underwent laparoscopic counterclockwise modular mesohepatectomy (LCMM) at our center. The LCMM approach standardizes the dissection sequence, optimizes vascular control, and utilizes Laennec’s capsule theory to facilitate safe and precise anatomical liver resection. Perioperative outcomes, including operative time, intraoperative blood loss, and postoperative complications, were assessed.ResultsA total of 12 patients with centrally located HCC underwent LCMM. The mean operative time was 253.66 ± 52.47 minutes, and the mean intraoperative blood loss was 177.91 ± 112.76 mL. No conversions to open surgery or intraoperative transfusions were required. The mean postoperative hospital stay was 9.83 ± 4.26 days. Postoperative complications occurred in three patients (one bile leakage, one pulmonary infection, and one posthepatectomy liver failure). No perioperative mortality occurred. The mean disease-free survival (DFS) was 18.75 months.ConclusionLCMM appears to be a technically effective and anatomically guided approach for managing centrally located HCC. It facilitates intraoperative control of key vascular structures and yields promising short-term oncological outcomes. Further prospective studies are warranted to confirm its long-term efficacy.